2019
DOI: 10.2139/ssrn.3487689
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA DIO3OS Binds to microRNA-130b to Restore Radiosensitivity in Esophageal Squamous Cell Carcinoma by Upregulating PAX9

Abstract: Background: Esophageal squamous cell carcinoma (ESCC) ranks as one of the most fatal cancers worldwide for its aggression and unsatisfactory survival rate. The long non-coding RNA (lncRNA)-microRNA (miRNA)-mRNA axis has been highlighted as a potency biomarker for enhancing the radiosensitivity of ESCC. Hence, we investigated the functional mechanism of the DIO3OS/miR-130b/paired box 9 (PAX9) axis in the radioresistance of ESCC cells. Methods: In cell experiments, we altered the miR-130b expression in ESCC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…DIO3OS may be the most important key m6AlncRNA in the development of many cancers. Many studies have shown that low DIO3OS expression promotes the occurrence and progression of cancers such as hepatocellular carcinoma, pancreatic carcinoma, and esophageal squamous cell carcinoma [37,39,50,51]. A recent study also suggested that CpG456 methylation downregulated DIO3OS expression leading to tumorigenesis and metastasis in NSCLC, which indicates that it might exhibit the similar CpG456 methylation in ‘driver‐gene‐negative’ LUAD [52].…”
Section: Discussionmentioning
confidence: 99%
“…DIO3OS may be the most important key m6AlncRNA in the development of many cancers. Many studies have shown that low DIO3OS expression promotes the occurrence and progression of cancers such as hepatocellular carcinoma, pancreatic carcinoma, and esophageal squamous cell carcinoma [37,39,50,51]. A recent study also suggested that CpG456 methylation downregulated DIO3OS expression leading to tumorigenesis and metastasis in NSCLC, which indicates that it might exhibit the similar CpG456 methylation in ‘driver‐gene‐negative’ LUAD [52].…”
Section: Discussionmentioning
confidence: 99%